2015
DOI: 10.1016/j.molcel.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

H3K4/H3K9me3 Bivalent Chromatin Domains Targeted by Lineage-Specific DNA Methylation Pauses Adipocyte Differentiation

Abstract: Bivalent H3K4me3 and H3K27me3 chromatin domains in embryonic stem cells keep active developmental regulatory genes expressed at very low levels and poised for activation. Here, we show an alternative and previously unknown bivalent modified histone signature in lineage-committed mesenchymal stem cells and preadipocytes that pairs H3K4me3 with H3K9me3 to maintain adipogenic master regulatory genes (Cebpa and Pparg) expressed at low levels yet poised for activation when differentiation is required. We show linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
215
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 195 publications
(236 citation statements)
references
References 54 publications
14
215
0
5
Order By: Relevance
“…A genome-wide analysis of chromatin states in embryonic stem cells (ES cells), mesenchymal stem cells and 3T3-L1 pre-adipocytes revealed that the bivalent trimethyl marks on histone H3 Lys residues (H3K4me3 and H3K27me3) at the Pparg and Cebpa gene loci are specific to ES cells and are not observed in mesenchymal stem cells or pre-adipocytes 30 . In preadipocytes, on the other hand, the bivalent H3K4me3 and H3K9me3 marks are found at the Pparg and Cebpa gene loci and seem to establish a ‘poised’ chromatin state that is prepared for active transcription upon induction (FIG.…”
Section: Chromatin Landscapes In Adipocytesmentioning
confidence: 99%
“…A genome-wide analysis of chromatin states in embryonic stem cells (ES cells), mesenchymal stem cells and 3T3-L1 pre-adipocytes revealed that the bivalent trimethyl marks on histone H3 Lys residues (H3K4me3 and H3K27me3) at the Pparg and Cebpa gene loci are specific to ES cells and are not observed in mesenchymal stem cells or pre-adipocytes 30 . In preadipocytes, on the other hand, the bivalent H3K4me3 and H3K9me3 marks are found at the Pparg and Cebpa gene loci and seem to establish a ‘poised’ chromatin state that is prepared for active transcription upon induction (FIG.…”
Section: Chromatin Landscapes In Adipocytesmentioning
confidence: 99%
“…Recently, another bivalent chromatin mark has been introduced by Matsumura et al, where H3K4me3 and H3K9me3 domains exist at promoters of mesenchymal stem cells (Matsumura et al, 2015). This unexpected existence of a bivalent state at enhancers with or without CpG islands has, to our knowledge, not been reported and may be exclusively an enhancer characteristic that does not exist at gene promoters or other functional elements.…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence of potentially conflicting signals was originally termed as “bivalency” to describe the co-existence of H3K27me3 and H3K4me3 on individual nucleosomes (Bernstein et al., 2006). Bivalency with respect to other histone marks was also very recently described for H3K4me3 and H3K9me3 modifications (Matsumura et al, 2015), suggesting that histone modification bivalency originally might be more common than previously realized but has not been investigated with respect to the generally repressive DNA methylation mark.…”
Section: Introductionmentioning
confidence: 91%
“…Emerging evidence indicates that bivalency poises genes for expression and is likely a key regulatory mechanism in transdifferentiation during lineage commitment as well as in dedifferentiation during onset and progression of cancer ( Fig. 1) (20)(21)(22)(23)(24). We propose that partial recapitulation of the bivalent chromatin landscape of pluripotent cells in some cancer types-termed "oncofetal epigenetic control" in this review-can offer novel avenues for the development of specific and selective diagnostic and therapeutic approaches.…”
mentioning
confidence: 85%
“…For example, trophoblast and endodermal stem cells demonstrate a pattern of bivalent H3K4me3/H3K9me3 modifications on lineage-specific genes that function independently of H3K4me3/H3K27me3 to regulate differentiation (211). Similarly, in mesenchymal stem cells, H3K4/H3K9me3 bivalent chromatin at several key adipogenic genes was demonstrated to keep lineage-specific genes poised, but repressed, until commitment to adipogenesis took place (21). It remains unclear how prevalent such "noncanonical bivalent domains" are and whether these are associated with gene regulation in specific cellular pathways.…”
Section: Options and Opportunitiesmentioning
confidence: 99%